PENGARUH DESIGN INTERIOR DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PESENKOPI DI KOTA MALANG (STUDI MAHASISWA JURUSAN ADMINISTRASI NIAGA POLITEKNIK NEGERI MALANG) - Rahmatu Rabiah; Mohammad Maskan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
The purpose of this research is to analyze he effect of interior design and the location of purchasing decisions at Pesenkopi in Malang City. This research is a quantitative study with variable interior design and location. This study used a questionnaire data collection technique using purposive sampling technique to 100 respondents of Malang Pesenkopi consumers. Then, the data were analyzed using multiple linear regression analysis, t test and F test. The results of the research show that Interior Design and Location has a percentage coefficient of determination or influence of 51.2% and Location is the dominant influence on purchasing decisions with a coefficient of 0.508 compared to Interior Design with a coefficient of 0.298.